Harnessing medically relevant metals onto water-soluble subphthalocyanines: towards bimodal imaging and theranostics1. Issue 7 (21st February 2015) - Bernhard, Yann; Winckler, Pascale; Perrier-Cornet, Jean-Marie; Decréau, Richard A.
<x xml:space="preserve">Abstract</x> Water-soluble subphthalocyanine (SubPc) - chelating ligands (DOTA, DTPA) conjugates were complexed with six metals relevant to medical imaging/therapies (MRI, PET, SPECT, RIT, NCT). Magneto-optical properties of the ditopic Gd complex and cellular microscopy studies were reported.